2021
DOI: 10.1096/fj.202001753r
|View full text |Cite
|
Sign up to set email alerts
|

Temporal regulation of tumor growth in nocturnal mammals: In vivo studies and chemotherapeutical potential

Abstract: Tumors of the nervous system including glioblastoma multiforme (GBM) are the most frequent and aggressive form of brain tumors; however, little is known about the impact of the circadian timing system on the formation, growth, and treatment of these tumors. We investigated day/night differences in tumor growth after injection of A530 glioma cells isolated from malignant peripheral nerve sheath tumor (MPNSTs) of NPcis (Trp53 +/− ; Nf1 +/− ) mice. Synchronized A530 cell cultures expressing typical glial markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 89 publications
6
33
0
Order By: Relevance
“…Similar results recently showed a reduction in PER1 expression in high-grade gliomas [222]. In agreement with these observations, tumors generated by injection of cells isolated from a malignant peripheral nerve sheath tumor exhibited lower Per1 mRNA levels than normal tissue [21]. One possible explanation linking the low levels of Per1 mRNA and protein with a higher tumor malignancy may be likely associated with the opposite relationship found between its expression and the phospholipid biosynthesis required for the genesis of the new membranes and other essential processes during cell growth and proliferation, as was observed in a non-malignant fibroblast cell line [161].…”
Section: Period 1 Genesupporting
confidence: 89%
See 3 more Smart Citations
“…Similar results recently showed a reduction in PER1 expression in high-grade gliomas [222]. In agreement with these observations, tumors generated by injection of cells isolated from a malignant peripheral nerve sheath tumor exhibited lower Per1 mRNA levels than normal tissue [21]. One possible explanation linking the low levels of Per1 mRNA and protein with a higher tumor malignancy may be likely associated with the opposite relationship found between its expression and the phospholipid biosynthesis required for the genesis of the new membranes and other essential processes during cell growth and proliferation, as was observed in a non-malignant fibroblast cell line [161].…”
Section: Period 1 Genesupporting
confidence: 89%
“…Recent results from our laboratory showed significant differences in Bortezomib efficacy on tumor-bearing mice when the drug was administered at the beginning of the day in the light phase or at night in the dark. We showed that a chemotherapeutic scheme in which a high dose (1.5 mg/kg) of Bortezomib was administered wholly inhibited tumor growth at both times; whereas a low dose of Bortezomib (0.5 mg/kg) displayed higher efficacy to impair tumor growth when delivered at night compared to diurnal treatment [21] (Figure 2). A recent retrospective study on GBM patients reported that the administration of TMZ in the morning was correlated with an increased OS in MGMT-methylated patients compared with those subjected to evening treatment.…”
Section: Chronotherapy As a Promising Strategy For Gbm Treatmentmentioning
confidence: 97%
See 2 more Smart Citations
“…Chronotherapy has emerged as a new concept that proposes the differential administration of drugs throughout the 24-h daytime to improve drug efficiency and reduce cancer toxicity and side effects of the treatment. This strategy has been applied only recently to treat CNS tumors because a differential response to the proteasome inhibitor Bortezomib was shown in a murine model [ 21 ] and that TMZ administration in human and murine GBM cells in culture is dependent on clock gene expression [ 22 ]. In this review, we analyze and discuss the current literature regarding GBM biology, the role of the circadian clock in tumor progression, specifically on GBM, and the potential of chronotherapy as an original approach to improve the treatment for this type of tumor.…”
Section: Introductionmentioning
confidence: 99%